Econometric modelling techniques and applications - Holly, Sean (Ed.); Weale, Martin (Ed.) (Cambridge Cambridge University Press, 2000)
Macroeconomic modelling hasbeen one of the most important and influential areas of economic research.this book presents contributors form the leading researchers working in this area.The book consider a wide range of issues.these includes how to observed
Keywords: Econometric models; Econometrics; Mathematical models